2010
DOI: 10.1097/ico.0b013e3181ca3293
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Lacunar Hydration Pattern After Corneal Cross Linking

Abstract: After riboflavin/UV-A cross linking of in vivo rabbit cornea, a characteristic lacunar hydration pattern can be observed in the anterior stroma with maximum cross linking, whereas diffuse edema is present in the adjacent areas without significant cross linking. The lacunar edema may explain the temporary demarcation of the anterior stroma after cross linking on biomicroscopy because of increased light scattering. The network pattern of cross linking may contribute to the elasticity of the cornea after cross li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 32 publications
(42 reference statements)
0
29
0
4
Order By: Relevance
“…This difference in edema pattern between the treated zone and the areas adjacent to it can serve as an explanation for the formation of the above-described demarcation line. By week 6 after the operation, the cellular structure appears to normalize [96]. Others reported the keratocyte loss to be more prolonged - up to 30 months postoperatively [97].…”
Section: Resultsmentioning
confidence: 99%
“…This difference in edema pattern between the treated zone and the areas adjacent to it can serve as an explanation for the formation of the above-described demarcation line. By week 6 after the operation, the cellular structure appears to normalize [96]. Others reported the keratocyte loss to be more prolonged - up to 30 months postoperatively [97].…”
Section: Resultsmentioning
confidence: 99%
“…After collagen cross-linking using riboflavin and UV-A, a lacunar honeycomb-like hydration pattern can be found in the anterior stroma with the maximum cross-linking effect, which is because of the prevention of interfibrillar cross-linking bonds in the positions of the apoptotic keratocytes [25]. The polygonal cross-linking network might contribute favorably to the biomechanical elasticity of the cross-linked cornea and to the demarcation of the anterior stroma after CXL on biomicroscopy [25], thus making lacunar edema a positive sign of efficient cross-linking.…”
Section: Complications Of CXLmentioning
confidence: 99%
“…The positive effect of CXL on CS was not evident in the early postoperative visit, which might be a consequence of an early temporary anterior stromal haze due to entrapped lacunar edema. 23,24 It has previously been reported that BSCVA and corneal topography indices improve after CXL. 4,7-10 Compared with baseline, we found a progressive improvement of the mean BSCVA over the first year after CXL that remained stable during the second year of follow-up.…”
Section: Discussionmentioning
confidence: 98%